Total Aortic Arch Replacement: Case Report of the first successful total arch replacement in Nepal and Review of contemporary techniques in arch surgery - Timala, Rabindra; Amatya, Ashish; Basnet, Nishes; Pradhan, Rupak; Joshi, Dikshya; Aryal, Marisha; Gautam, Navin (Nepalese Heart Journal, 2021)
Aortic arch replacement is formidable cardiac surgery that is fraught with complications like brain injury, coagulopathy along with high mortality. Over the past several years, various techniques like deep hypothermic circulatory arrest, retrograde cerebral perfusion, and selective antegrade cerebral perfusion along with branched graft techniques have been developed with better early outcomes. We share our experience of successful replacement of ascending and total aortic arch in a 60 years old female, who presented with ascending and aortic arch aneurysm.